Have AI-Enhanced Telemedicines in Indonesia Adopted the Principles of Personal Data Protection? - Kevin Raihan; Sinta Dewi Rosadi (Yustisia)
Artificial   Intelligence   (AI)-enhanced   telemedicines   pertains to legal problems especially on the protection of personal data considering the its nature. However, there has not been any research specifically examining the protection of personal data in in Indonesia with the perspective of Law Number 27 of 2022 regarding Personal Data Protection (PDP Law), specifically regarding the analysis of personal data protection principles (PDP Principles). Therefore, this research aimed to evaluate and analyze the practice of telemedicines in Indonesia on the adoption of PDP Principles from the perspective of PDP Law. This research is legal research with statutory and comparative approach related to AI and personal data protection issues in the AI-enhanced telemedicines in Indonesia. The findings show that telemedicine applications is categorized as personal data controller (data controller). The obligation of telemedicine application as a data controller obligates them to comply with the personal PDP Principles as regulated in the PDP Law. Several telemedicines in Indonesia have not yet effectively adopted PDP Principles in their privacy policy. The article concludes that the telemedicines applications must update their privacy policy to comply with PDP Principles and the government of Indonesia should accelerate the enactment of implementing regulation for the PDP Law.